Recombinant osteoprotegerin decreases tumor burden and increases survival in a murine model of multiple myeloma. - Vanderkerken, K; De Leenheer, E; Shipman, C; Asosingh, K; Willems, A; Van Camp, B; Croucher, P (2003)
The aim of the present study was to determine whether modifying the local bone environment with osteoprotegerin (OPG), the soluble decoy receptor for receptor activator of nuclear factor-kappaB (RANK) ligand, could affect tumor burden and survival in the 5T33MM murine model of multiple myeloma. Treatment of mice, injected with 5T33MM cells, with recombinant OPG (Fc-OPG) caused a significant decrease in serum paraprotein and tumor burden and a significant increase in time to morbidity. This was associated with a decrease in osteoclast number in vivo but had no effect on apoptosis and proliferation of 5T33MM cells in vitro. These data indicate that targeting the bone microenvironment by inhibiting the interaction between RANK ligand and RANK with Fc-OPG not only inhibits the development of myeloma bone disease but also decreases tumor growth and increases survival.